Associations of genetic polymorphisms within MALAT1, UCA1, FAM211A-AS1 and AC000111.6 with genetic susceptibility to rheumatoid arthritis. (2nd October 2020) - Zhang, Zhen; Zhang, Wei; Wen, Qin-Wen; Wang, Ting-Hui; Qin, Wen; Huang, Hua; Mo, Yi-Jun; Wu, Xiu-Di; Cen, Han
Abstract: Recently, several long non-coding RNAs (lncRNAs) including MALAT1, UCA1, ENST00000483588, and ENST00000456270 have been implicated in the pathogenesis of rheumatoid arthritis (RA), and we hypothesized that polymorphisms within these lncRNA genes might be genetic modifiers for the development of RA. A total of 10 potentially functional single-nucleotide polymorphisms (SNPs) were selected and genotyped in 1198 participants, including 594 RA patients and 604 healthy controls. Significant associations of FAM211A-AS1 rs2882581 (G vs. A, OR = 1.31, 95%CI 1.07–1.62, p  = .01; G/G + A/G vs. A/A, OR = 1.40, 95%CI 1.08–1.83, p  = .01), rs3744281 (T vs. A, OR = 1.25, 95%CI 1.02–1.54, p  = .03; T/T vs. A/T + A/A, OR = 1.69, 95%CI 1.01–2.82, p  = 4.59 × 10 −2 ), and rs3760235 (A vs. G, OR = 1.32, 95%CI 1.04–1.68, p  = .02; A/A vs. A/G + G/G, OR = 1.32, 95%CI 1.00–1.74, p  = 4.89 × 10 −2 ) with RF-positive RA were found. Functional annotation results indicated that these identified polymorphisms might regulate the expression of FAM211A-AS1 and nearby genes via impacting on transcription factor binding. Taken together, our results indicated that FAM211A-AS1 rs2882581, rs3744281, and rs3760235 were involved in the genetic background of RF-positive RA.